THE EFFECTIVENESS OF USING SELF-REFLECTION TECHNIQUE TOWARDS STUDENTS’ WRITING ABILITY AN EXPERIMENTAL STUDY AT SMA 15 ADIDARMA BANDA ACEH - Irmawati, Wirda; Mulyani; Syahputra, Mulyadi (Jurnal Ilmiah Mahasiswa Pendidikan, 2022)
This research focused on using self-reflection technique toward students’ writing ability. The purpose of this study was to find out whether or not self-reflection technique effective to improve students’ writing ability at SMA 15 Adidarma Banda Aceh. The researcher used experimental quantitative research as the method in this study. The test was used as the instrument. The result showed that there is significant difference score of writing recount text between the students taught by using self reflection technique and the students taught without using self reflection technique. After using the self reflection technique in experimental class, the researcher found the different score of pre-test and post-test. The mean score of post-test was 69.5 and pre-test got 44.9. The result showed that t-score (13.15) is higher than critical at level significant 0.05 (1.83311) for one test. It means that there was significant different between two test. The alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Therefore, it answers the first research question that the use of self reflection technique is effective to improve the students’ ability in writing recount text. However, even if there is a significant difference between pre-test and post-test, unfortunately it is not good enough to make the students passed the examination of writing because the minimun score of writing examination was 75. But, the students got the average score only 69.5. It means that the students still have not good capability in writing especially in recount text.